Phase 1b study of galunisertib and ramucirumab in patients with advanced hepatocellular carcinoma. (2nd April 2021) - Harding, James J.; Do, Richard K.; Yaqubie, Amin; Cleverly, Ann; Zhao, Yumin; Gueorguieva, Ivelina; Lahn, Michael; Benhadji, Karim A.; Kelley, Robin K.; Abou‐Alfa, Ghassan K.
Abstract: Background: Preclinical data suggest that vascular endothelial growth factor (VEGF) and transforming growth factor (TGF)‐β signaling interact to stimulate angiogenesis and suppress antitumor immune responses. Thus, combined inhibition of both pathways may offer greater antitumor activity compared with VEGF‐targeted antiangiogenic monotherapy against hepatocellular carcinoma (HCC). Methods: This is a multicenter, open‐label, phase 1b study of galunisertib, an inhibitor of TGF‐β receptor 1, and ramucirumab, an anti‐VEGF receptor 2 antibody, in patients with advanced HCC aiming to define the maximum tolerated dose (MTD). Secondary objectives included safety, pharmacokinetics (PK), antitumor efficacy, and plasma alpha‐fetoprotein and TGF‐β kinetics. Dose escalation employed a 3 + 3 design. Patients received galunisertib at 80 mg (cohort 1) or 150 mg (cohort 2) orally twice a day on days 1–14 of a 28‐day cycle combined with ramucirumab 8 mg/kg intravenously every 2 weeks. Results: Eight patients were enrolled: three in cohort 1 and five in cohort 2 (two patients were unevaluable due to rapid disease progression and replaced). No dose‐limiting toxicities were observed. Treatment‐related adverse events (AEs) of any grade in ≥2 patients included nausea (25%) and vomiting (25%). There was one Grade 3 treatment‐related AE, a cerebrovascular accident possibly related to ramucirumab. Galunisertib exposure was dose‐proportional and not affected by ramucirumab. The RECIST version 1.1 objective response rate and disease control rate were 0% and 12.5%, respectively. Conclusion: Combination therapy was safe and tolerable and displayed favorable PK. The MTD was established at galunisertib at 150 mg orally twice a day and ramucirumab 8 mg/kg intravenously every 2 weeks. The results do not support the preclinical hypothesis that blocking TGFβ signaling enhances efficacy of VEGF‐targeted therapy; thus further clinical development was halted for the combination of galunisertib and ramucirumab. Abstract : The combination of galunisertib (up to 150 mg twice as day) and ramucirumab 8 mg/kg intravenously every 2 weeks (standard dose) was safe and tolerable and displayed favorable pharmacokinetics in patients with advanced hepatocellular carcinoma. The results do not support the preclinical hypothesis that blocking transforming growth factor‐beta signaling enhances efficacy of VEGF‐targeted therapy; thus further clinical development was halted for the combination of galunisertib and ramucirumab.